Personality, Communication, and Depressive Symptoms Across the Transition to Parenthood: A Dyadic Longitudinal Investigation. Issue 2 (March 2015) - Marshall, Emma M.; Simpson, Jeffry A.; Rholes, W. Steven
Abstract: This study adopted a person (actor) by partner perspective to examine how actor personality traits, partner personality traits, and specific actor by partner personality trait interactions predict actor's depressive symptoms across the first 2 years of the transition to parenthood. Data were collected from a large sample of new parents (both partners in each couple) 6 weeks before the birth of their first child, and then at 6, 12, 18, and 24 months postpartum. The results revealed that higher actor neuroticism and lower partner agreeableness predicted higher levels of depressive symptoms in actors. Moreover, the specific combination of high actor neuroticism and low partner agreeableness was a particularly problematic combination, which was intensified when prepartum dysfunctional problem‐solving communication and aggression existed in the relationship. These results demonstrate the importance of considering certain actor by partner disposition pairings to better understand actors' emotional well‐being during major life transitions. Copyright © 2015 European Association of Personality Psychology